2013
DOI: 10.1016/j.retrec.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The interurban DRAG-Spain model: The main factors of influence on road accidents in Spain

Abstract: This paper presents the results of applying DRAG methodology to the identification of the main factors of influence on the number of injury and fatal accidents occurring on Spain's interurban network. Nineteen independent variables have been included in the model grouped together under ten categories: exposure, infrastructure, weather, drivers, economic variables, vehicle stock, surveillance, speed and legislative measures. Highly interesting conclusions can be reached from the results on the basis of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Finally, the average annual precipitation, as a meteorological variable, is significant and has a negative sign. This relationship has been previously documented and is considered to be the result of greater driving caution in the presence of rain [51,69].…”
Section: Meteorological Variablessupporting
confidence: 53%
See 4 more Smart Citations
“…Finally, the average annual precipitation, as a meteorological variable, is significant and has a negative sign. This relationship has been previously documented and is considered to be the result of greater driving caution in the presence of rain [51,69].…”
Section: Meteorological Variablessupporting
confidence: 53%
“…With regard to the composition of the road infrastructure, a significant negative relationship was derived for the proportion of motorways, as seen elsewhere in the literature [51,52,54,95]. Albalate and Bel [95] indicated that only a greater proportion of highways in the road network had beneficial effects in reducing mortality, while the extension of the rest of the network did not clearly affect road safety.…”
Section: Explanatory Variables For Transport-specific Factorsmentioning
confidence: 59%
See 3 more Smart Citations